2001
DOI: 10.1046/j.1365-2753.2001.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

How to validate clinically important change in health‐related functional status. Is the magnitude of the effect size consistently related to magnitude of change as indicated by a global question rating?

Abstract: Some clinical trials perform repeated measurement over time and estimate clinically relevant change in an instrument's score with global ratings of perceived change or so-called transition questions. The conceptual and methodological difficulties in estimating the magnitude of clinically relevant change over time in health-related functional status (HRFS) are discussed. This paper investigates the concordance between the amount of serially assessed change with effect size estimates (the researcher's perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 47 publications
3
55
0
4
Order By: Relevance
“…It was shown that, according to an external criterion, SRM ≥ 0.20 reflects a clinical relevant change. 37 …”
Section: Discussionmentioning
confidence: 99%
“…It was shown that, according to an external criterion, SRM ≥ 0.20 reflects a clinical relevant change. 37 …”
Section: Discussionmentioning
confidence: 99%
“…A interpretação convencional dos valores de TE é: 0,2 = TE pequeno; 0,5 = TE médio; 0,8 = TE grande 22 . Todas as variáveis mostraram TE grande (Tabela 2).…”
Section: Resultsunclassified
“…Impressions of change could be used as anchors to define worthwhile effects from the perspectives of the clinicians and patients. 12,18,23 This and similar methodologies are increasingly used in different areas of medicine 3,24,25 and pain management, 11,26 and are starting to be explored in SCI. 27 However, this type of research in SCI requires large numbers of participants, some of whom need to show notable change over time.…”
Section: Discussionmentioning
confidence: 99%